Wild Neighborhood - Henricksson, John (Book collections on Project MUSE., 1997)
Illustrated by Betsy BowenBeautifully illustrated by award-winning artist Betsy Bowen, author of Antler, Bear, Canoe: A Northwoods Alphabet Year, this collection of elegantly written essays celebrates the creatures that share our place in the woods. From kitchen-table gossip about the black bear's recent attempts to raid the bird feeder, to the retelling of Native American myths about the mischievous raven, Henricksson illustrates his respect, humor, and love of northwoods creatures.